PENGEMBANGAN LEMBAR KERJA (LK) BERBASIS INKUIRI TERBIMBING PADA PEMBUATAN TEMPE DAUN SINGKONG - praatama, Agung; Kurniati, Tuti; sa'adah, sumiyati (Jurnal BIOEDUIN, 2019)
The learning process to be understood requires that learning activities be carried out by practicum so that it has better results. Learning resources and learning media that are capable of supporting practicum are worksheets (LK). The existence of LK provides a considerable influence in the teaching and learning process. This study aims to develop a guided inquiry based LK on making cassava leaf tempeh. To determine the results of the LK validation test and analyze the organoleptic test, the research method used is research and development with a 3D model. The research was conducted at the integrated laboratory of Sunan Gunung Djati UIN Bandung. The research subjects consisted of expert validators, limited test respondents, and organoleptic test panelists. The validation results by three validators are 3.5; 2.9; and 2.9 with an average of 3.11 and a percentage of 86.7%; 73.3%; and 73.3% and rhitung count 0.62 or categorized as valid. The test results are limited to LK at 3.54 and rhitung count 1.61. The organoleptic test results obtained the best treatment of each characteristic, namely the average characteristic of color, texture, aroma, compactness, and highest taste of 3.40; 2.93; 3.17; 3.46; and 4.35 with the best treatment, each d2w1, d1w2, d1w2, d1w2, d2w2. So that it can be concluded as a whole LK that has been compiled and developed in making cassava leaf tempeh including good categories and fulfilling the eligibility criteria can be applied to practicum. Â